Looking at wiki, I want to

$p_A (t) = \sum_{k=0}^n t^{n-k} (-1)^k \operatorname{tr}(\Lambda^k A) $

where ${\displaystyle \operatorname {tr} (\Lambda ^{k}A)={\frac {1}{k!}}{\begin{vmatrix}\operatorname {tr} A&k-1&0&\cdots &\\\operatorname {tr} A^{2}&\operatorname {tr} A&k-2&\cdots &\\\vdots &\vdots &&\ddots &\vdots \\\operatorname {tr} A^{k-1}&\operatorname {tr} A^{k-2}&&\cdots &1\\\operatorname {tr} A^{k}&\operatorname {tr} A^{k-1}&&\cdots &\operatorname {tr} A\end{vmatrix}}~.}$

Wikipedia states this can be proven via the language of exterior algebra, How?

  • $\begingroup$ What are you looking for? A proof of the formula for $\mathrm{tr}(\Lambda^k A)$ using exterior algebra, or a proof of the formula for $p_A(t)$? $\endgroup$ – Nick Jan 13 at 6:44
  • $\begingroup$ @Nick. I want to know both, but the purpose of this post is to know the former one. $\endgroup$ – phy_math Jan 13 at 11:46

Let $v_1,\dots,v_n$ be a basis of $V$, consisting of eigenvectors with eigenvalues $\lambda_1,\dots,\lambda_n$. Then $\mathrm{tr}(A) = \sum \lambda_i$.

As a basis for $\Lambda^k V$, you can take the collection of all $v_{i_1} \wedge \cdots \wedge v_{i_k}$, where $i_1 < \cdots < i_k$. Since by definition, $$ (\Lambda^k A)(v_{i_1} \wedge \cdots \wedge v_{i_k}) = (Av_{i_1}) \wedge \cdots \wedge (Av_{i_k}) = \lambda_{i_1} \cdots \lambda_{i_k} \, v_{i_1} \wedge \cdots \wedge v_{i_k} $$ you see that this basis also consists of eigenvectors, with corresponding eigenvalues $\lambda_{i_1} \cdots \lambda_{i_k}$. So the trace of $\Lambda^k A$ is the sum of its eigenvalues, giving $$ \mathrm{tr}(\Lambda^k A) = \sum_{i_1 < \cdots < i_k} \lambda_{i_1} \cdots \lambda_{i_k} $$ If you are familiar with symmetric polynomials, this is the "elementary symmetric polynomial" $e_k(x_1,\dots,x_n)$, evaluated at $x_i = \lambda_i$ for all $i$.

On the other hand, $\mathrm{tr}(A^k) = p_k(\lambda_1,\dots,\lambda_n)$, where these are the "power sum symmetric polynomials" $p_k(x_1,\dots,x_n) = x_1^k + x_2^k + \cdots + x_n^k$.

The determinant formula you quoted from Wikipedia follows from the well-known "Newton Identity", which tells how to express the two types of symmetric polynomials in terms of the other ones. See the Wikipedia page for Newton identity for more info.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.